2016
DOI: 10.1007/s10730-016-9305-0
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Current Advance Care Planning Paradigm: Advocating for a Communications-Based Approach

Abstract: The purpose of advance care planning (ACP) is to allow an individual to maintain autonomy in end-of-life (EOL) medical decision-making even when incapacitated by disease or terminal illness. The intersection of EOL medical technology, ethics of EOL care, and state and federal law has driven the development of the legal framework for advance directives (ADs). However, from an ethical perspective the current legal framework is inadequate to make ADs an effective EOL planning tool. One response to this flawed AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
19
0
4
Order By: Relevance
“…While individual consideration of future EoL issues is also likely to take place in Sweden, the lack of systematic practice motivates consideration of the Swedish context itself as ACP-naive on a collective level. Based on previous international research and adapted to the Swedish context, the approach to ACP in this research project: “Advance care planning in Sweden” (SweACP), is based on three cornerstones as it is (a) conversation-based ( Sudore & Fried, 2010 ; Vearrier, 2016 ), (b) initiated early ( Howard et al, 2015 ; Zwakman et al, 2018 ), and (c) community-based, that is, taking place outside the health and social care systems ( Litzelman et al, 2017 ; Somes et al, 2018 ).…”
mentioning
confidence: 99%
“…While individual consideration of future EoL issues is also likely to take place in Sweden, the lack of systematic practice motivates consideration of the Swedish context itself as ACP-naive on a collective level. Based on previous international research and adapted to the Swedish context, the approach to ACP in this research project: “Advance care planning in Sweden” (SweACP), is based on three cornerstones as it is (a) conversation-based ( Sudore & Fried, 2010 ; Vearrier, 2016 ), (b) initiated early ( Howard et al, 2015 ; Zwakman et al, 2018 ), and (c) community-based, that is, taking place outside the health and social care systems ( Litzelman et al, 2017 ; Somes et al, 2018 ).…”
mentioning
confidence: 99%
“…The ability of a living will to accurately predict patients’ future preferences has been fundamentally questioned for decades 32 . Studies have even shown inconsistencies between patients’ documented preferences and their verbally expressed ones 33 . By completing a living will, patients sign a document requesting a plan of care to be implemented at a time when they can no longer evaluate whether the document continues to be consistent with their values.…”
Section: Risksmentioning
confidence: 99%
“…In a study that evaluated POLST use by a hospice program, the greatest barrier to its use was understanding and explaining the form 42 . In one study, only 56% of patients correctly defined DNR and only 26% correctly defined CPR 33 . Recent studies have pointed out the existence of a minority of POLST forms with inconsistent or incompatible selections, 43 and that the POLST on record does not always correlate to the patient's true wishes 44 .…”
Section: Risksmentioning
confidence: 99%
“…51 Not offering CPR is similar to unilateral do-not-resuscitate (DNR) orders that are initiated by a physician without patient or surrogate consent. Protocols and orders that withhold resuscitation are ethically and legally complex and logistically difficult to implement, 52 and therefore not currently appropriate for prehospital care.…”
Section: Ethics Of Delaying or Withholding Medical Care Or Transportmentioning
confidence: 99%